2018
DOI: 10.1116/1.5022145
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial interactions with biomembranes: Bridging the gap between soft matter models and biological context

Abstract: Synthetic polymers, nanoparticles, and carbon-based materials have great potential in applications including drug delivery, gene transfection, in vitro and in vivo imaging, and the alteration of biological function. Nature and humans use different design strategies to create nanomaterials: biological objects have emerged from billions of years of evolution and from adaptation to their environment resulting in high levels of structural complexity; in contrast, synthetic nanomaterials result from minimalistic bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…However, despite the remarkable developments of recent methodologies, most of all nanocarriers' action is associated with a number of unwanted side effects that diminish their efficient use in nanomedicine. This highlights some critical issues in the design and engineering of nanocarrier systems for biotechnology applications, arising from the complex environment and multiform interactions established within the specific biological media [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the remarkable developments of recent methodologies, most of all nanocarriers' action is associated with a number of unwanted side effects that diminish their efficient use in nanomedicine. This highlights some critical issues in the design and engineering of nanocarrier systems for biotechnology applications, arising from the complex environment and multiform interactions established within the specific biological media [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A similar behaviour has been recently reported by Montis et al who showed that cationic AuNPs induce more drastic effects on zwitterionic and negatively charged membranes than anionic and PEG-coated AuNPs 25 . Moreover, the properties of the surrounding medium, such as pH, temperature, ionic strength, macromolecular crowding, and viscosity can modify many important characteristics of NPs such as surface charge, solubility and colloidal stability, and also can modulate their biological activity 21,26,27 . The considerably large number of parameters influencing the NP behaviour along with the complexity of biological membranes, makes the understanding of NP-membrane interactions very challenging.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The development of novel mechanisms for the delivery of drugs to biological cells has been the subject of intense study in recent years [1][2][3][4][5][6] . For small drug molecules the main barrier to efficient delivery is typically the cell membrane lipids 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…NPs have demonstrated a level of effectiveness through multiple applications in targeted therapy 5,11,12 . However, there are open questions regarding the physical mechanism of how NPs interact with cell membranes, notably the role of the local diversity in the membrane itself and within the cytoplasm of the cell interior 6,10 . For example, phospholipid molecules affect the assembly of the bilayer due to the varying degrees of saturation of the tailgroups, variations in tail length, and/or changes in headgroup functionality.…”
Section: Introductionmentioning
confidence: 99%